Health status, functional limitations and disability: Changes in Poland - Stanislawa Golinowska; Agnieszka Sowa (Center for Social and Economic Research (CASE), 2012)
The social changes in Poland over the last two decades have had an impact on many dimensions of life, including on important elements of human capital, such as health and functional and instrumental daily activities. This article contains an overview of the available data and indicators on health status, morbidity and disability. It presents the changes in the level of functional and legal disability and aims to show the reasons for these trends. Functional disability is highlighted as one of the major challenges for social and health policy in the next few decades in the context of dynamic aging.
Keywords: I10; I12; I18; 330; health status; legal disability; functional disability; Activities of Daily Living (ADL); Instrumental Activities of Daily Living (IADL); chronic diseases; mental health; injuries; ageing; Gesundheit; Krankheit; Morbidität; Behinderte; Sterblichkeit; Polen